Primary malignant melanoma of the lung: A case report - Yamamoto, Yoko (Mol Clin Oncol, 2017)
Malignant melanoma involving the respiratory tract is nearly always metastatic from a cutaneous lesion. Primary malignant melanoma of the lung (PMML) is very rare. We herein report the case of a 61-year-old female patient with PMML who presented with a small nodule in the lower lobe of the left lung on chest computed tomography. As an intraoperative diagnosis of malignant melanoma was made, left lower lobectomy with systematic lymph node dissection were performed. Pathologically, there were no lymph node or intrapulmonary metastases. Lesions other than the pulmonary nodule were not detected throughout the comprehensive postoperative examination of all organs. Thus, the patient was followed up regularly as an outpatient. However, 1 year after the operation, multiple organ metastases developed. The patient's condition rapidly deteriorated and she succumbed to the disease 15 months after the operation, despite intensive chemo-immunotherapy.